Fatores críticos de sucesso da estratégia para desempenho superior em hospitais privados - Luciana Faluba Damazio (2011)
The health sector has been the focus of attention for the past decades, especially in terms of its growth and technological development. In the current healthcare model, the General Hospitals achieved a distinguished position as leading service providers, acting as the health system core. The complexity of the hospital infrastructure in current days includes several medical specialties, high technological development, new forms of patient care and changes in the external environment of such institutions, that require the exercise of strategic managementaiming to assure the survival and sustainability of the hospitals. The understanding of why some strategic choices produce better results than others is a central research issue in the field of strategic management, particularly in the universe of private organizations immersed in thelogic of revenue generation to ensure business survival. The main objective of this study was to identify which strategic conducts adopted by leaders, considering both content and process, that would explain a significantly superior performance. Thus, a qualitative research wasconducted by taking as field of study hospitals associated to Associacao Nacional de Hospitais Privados (ANAHP), that are private institutions that are acknowledged superior performance, aiming to identify the critical success factors, i.e, the strategic management practices that have more influence on superior performance. Taking the same field of study, aquantitative survey was also conducted to identify practices related to performance. The results obtained by those two methodological steps were convergent and pointed out to a valuation of intangible aspects, especially those resulting from practices associated with the content of the strategy.